2017
DOI: 10.1371/journal.pone.0175985
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of GnRH antagonist protocol versus GnRH agonist long protocol in patients with normal ovarian reserve: A systematic review and meta-analysis

Abstract: ObjectiveTo evaluate the effectiveness and safety of gonadotropin-releasing hormone antagonist (GnRH-ant) protocol and gonadotropin-releasing hormone agonist (GnRH-a) long protocol in patients with normal ovarian reserve.MethodsWe searched the PubMed (1992–2016), Cochrane Library (1999–2016), Web of Science (1950–2016), Chinese Biomedical Database (CBM, 1979–2016), and China National Knowledge Infrastructure (CNKI, 1994–2016). Any randomized controlled trials (RCTs) that compared GnRH-ant protocol and GnRH-a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 44 publications
7
50
1
1
Order By: Relevance
“…However, the effectiveness of antagonists is still under debate. According to multiple studies comparing a GnRH agonist protocol and GnRH antagonist protocol, effectiveness, the number of oocytes retrieved and the number of embryos obtained are significantly lower when the antagonist is used (Wang et al, 2017). Furthermore, the cycle cancellation rate seems higher in women who received GnRH antagonist protocols compared with GnRH agonist protocols (Kahyaoğlu et al, 2017).…”
Section: Conventional Protocols For Ovarian Stimulation and The Role mentioning
confidence: 99%
“…However, the effectiveness of antagonists is still under debate. According to multiple studies comparing a GnRH agonist protocol and GnRH antagonist protocol, effectiveness, the number of oocytes retrieved and the number of embryos obtained are significantly lower when the antagonist is used (Wang et al, 2017). Furthermore, the cycle cancellation rate seems higher in women who received GnRH antagonist protocols compared with GnRH agonist protocols (Kahyaoğlu et al, 2017).…”
Section: Conventional Protocols For Ovarian Stimulation and The Role mentioning
confidence: 99%
“…There is also a risk for thromboembolic events, which is increased in the presence of pregnancy and OHSS. Recent reports of the occurrence of OHSS and thromboembolism in different populations have reported rates of less than 0.5% [4], meaning these adverse events (AEs), although important, occur rarely during ovarian stimulation with r-hFSH [4,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is still controversial about the e cacy of GnRH-a and GnRH-ant protocols with fresh ET. Several studies suggested that the pregnancy rate, ongoing pregnancy rate and live birth rate of fresh transfer cycles were lower in the GnRH-ant protocol than in the GnRH-a protocol (3,18), whereas other studies showed no signi cant difference (2,19). Furthermore, implantation is one of the most important steps to achieve live birth, therefore it is considered as an important indicator to the e cacy of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gonadotropin-releasing hormone agonist (GnRH-a) has been used since the early 1980s and plays an important role in controlled ovarian stimulation (COS) (1). Currently, GnRH antagonist (GnRH-ant) protocol is widely used due to its shorter treatment time, fewer injections and lower ovarian hyperstimulation syndrome (OHSS) rate than GnRH-a protocol (2). However, the standard GnRH-a long protocol is still one of the key down regulation protocol in China, due to its steady and higher clinical pregnancy rate in fresh embryo transfer (ET) in vitro fertilization (IVF) patients (3).…”
Section: Backgoundmentioning
confidence: 99%